Improving perception and confidence towards bystander cardiopulmonary resuscitation and public access automated external defibrillator program: how does training program help? - Liaw, Siew Yee; Chew, Keng Sheng; Ahmad, Zulkarnain; Wong, Shirly Siew Ling; Nariman Singmamae @ Nariman, Hama Sanamay; Dev Nath, Kaushal; Chan, Hiang Chuan (BMC Springer Nature, 2020)
Background